2009
DOI: 10.1007/s12564-009-9018-z
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation study on the educational value of teaching practicum in secondary schools

Abstract: The purpose of this study is to evaluate the educational value of teaching practicum in secondary schools. For this purpose, on the basis of literature review and interviews, three evaluation criteria for measuring educational value of teaching practicum are constructed as follows: (1) practical teaching competence, (2) readiness for teacher, and (3) maturity in character. A total of 29 preservice teachers in the College of Education at Seoul National University in South Korea participated voluntarily in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Such programmes have been established to bridge possible gaps between needs and expectations (Donina & Luka, 2014). In this regard, a study was conducted by Baek and Ham (2009) which suggested that training plays a significant role in developing teachers' teaching competence and maturity, and paves the way for trainees to master practical situations. Harvey and Bowers-Brown (2003) believe that training is viewed as a springboard for better learning, experience, and knowledge.…”
Section: Previous Studies On Pre-service Teachers Training and Gendermentioning
confidence: 99%
“…Such programmes have been established to bridge possible gaps between needs and expectations (Donina & Luka, 2014). In this regard, a study was conducted by Baek and Ham (2009) which suggested that training plays a significant role in developing teachers' teaching competence and maturity, and paves the way for trainees to master practical situations. Harvey and Bowers-Brown (2003) believe that training is viewed as a springboard for better learning, experience, and knowledge.…”
Section: Previous Studies On Pre-service Teachers Training and Gendermentioning
confidence: 99%
“…Preservice teacher preparatory programs generally combine observation and other research activities to help participants in their initial encounters with their future profession and with no doubt, observation as a key element in teachers' investigation emerges as one of the most important practices to help future teachers learn (Gonzalez, 2005). Baek and Ham (2009) suggest that recent researches on teaching practicum focuses on four themes: a) pre-service teacher's satisfaction, b) pre-service teacher's teaching performance, c) pre-service teacher's efficacy and d) pre-service teacher's understanding school as a field. Focusing on a different aspect, Baek and Ham (2009) then investigates the educational value of teaching practicum in secondary school.…”
Section: Related Researchmentioning
confidence: 99%
“…Baek and Ham (2009) suggest that recent researches on teaching practicum focuses on four themes: a) pre-service teacher's satisfaction, b) pre-service teacher's teaching performance, c) pre-service teacher's efficacy and d) pre-service teacher's understanding school as a field. Focusing on a different aspect, Baek and Ham (2009) then investigates the educational value of teaching practicum in secondary school. Referring to the results Bake and Ham argued that the teaching practicum had significantly improved pre-service teachers' practical teaching competence, readiness for teacher, and maturity in character, which implies that teaching practicum, is essentail in language teacher education programs.…”
Section: Related Researchmentioning
confidence: 99%